2016
DOI: 10.1016/j.msea.2015.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hydrogen assisted cracking in acicular ferrite using site-specific micro-fracture tests

Abstract: Hydrogen assisted cracking (HAC) is a common type of failure mechanism that can affect a wide range of metals and alloys. Experimental studies of HAC are cumbersome due to various intrinsic and extrinsic parameters and factors (associated with stress, hydrogen and the materials microstructure) contributing to the hydrogen crack kinetics. The microstructure of many materials consists of diverse constituents with characteristic features and mechanical properties which only occur in very small material volumes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
14
0
3
Order By: Relevance
“…During fracturing, AF can deflect crack propagation, which consumes the crack-propagation energy. The crack-arresting property is improved, which results in good DWTT properties [8][9][10]. Hence, it is necessary to establish the effect of UFC on AF in different heavy-gauge pipeline steel positions.…”
Section: Introductionmentioning
confidence: 99%
“…During fracturing, AF can deflect crack propagation, which consumes the crack-propagation energy. The crack-arresting property is improved, which results in good DWTT properties [8][9][10]. Hence, it is necessary to establish the effect of UFC on AF in different heavy-gauge pipeline steel positions.…”
Section: Introductionmentioning
confidence: 99%
“…TMCP promotes the formation of an acicular ferrite (AF)-based microstructure, which is the preferred microstructure for pipe steels. Steels with AF microstructure normally possess higher strength and toughness, as well as superior stress corrosion and fatigue resistance than steels with ferrite and pearlite (P) microstructure [1,2]. API X52 steel is used widely as pipeline material in Australia and other countries.…”
Section: Introductionmentioning
confidence: 99%
“…As shown with red circle, the SCC crack is deflected about 45 • when it reaches grain number 30. Calculation of misorientation between grains number (30,31) and (31,32) proves that the misoriatation angles between them are 12.3 • and 36.1 • , respectively. This proves why the SCC crack deflects when it reaches grain number 30.…”
Section: Effect Of Crystallographic Texture and Meso-texture On Scc Smentioning
confidence: 88%
“…Besides the SCC phenomenon, the SIF plays a key role in HIC crack propagation in pipeline steels. Costin et al [31] reported that the threshold SIF (Kth) range for crack propagation is between 1.56 MPa√ and 4.36 MPa√ . This range is lower than the Kth value which is calculated for ferrous alloys.…”
Section: Role Of Stress Intensity Factor (Sif) In Scc and Hic Crack Pmentioning
confidence: 99%